William Adams correspondence - Adams, William, active 1776.
ALS (Windsor, Md.; 1776 June 30) from Adams to the president of the Maryland Convention explaining his absence at recent meetings.
Delegate to the Maryland Convention.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Maryland. -- Convention; Maryland -- History -- Revolution, 1775-1783.; Legislators -- Maryland